2017
DOI: 10.4067/s0718-48082017000100010
|View full text |Cite
|
Sign up to set email alerts
|

Efectos secundarios de la medicación antipsicótica y calidad de vida en pacientes con esquizofrenia latinoamericanos

Abstract: Efectos secundarios de la medicación antipsicótica y calidad de vida en pacientes con esquizofrenia latinoamericanosResumen el estudio describe la relación entre los efectos secundarios a la medicación y la calidad de vida en pacientes con esquizofrenia. la muestra contó con 253 pacientes de los servicios públicos de salud Mental de Bolivia, perú y chile quienes fueron evaluados con la escala Barnes de acatisia (eBa); la escala de simpson-angus (sas) y el cuestionario de calidad de Vida (sQol-18). ambas escala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous research has shown that low adherence to psychiatric medication treatment affects the performance of domains associated with social cognition. These domains include Theory of Mind (TOM) and other neuropsychological functions such as verbal memory and executive functions (Zhang et al, 2016;Caqueo et al, 2017;El-Missiry et al, 2015). This demonstrates the relevance of the topic under the findings provided by previous research, which indicates the scientific importance that neurocognitive processes in schizophrenia and their relationship with medication adherence are acquiring.…”
Section: Issn-l: 2027-1786mentioning
confidence: 56%
“…Previous research has shown that low adherence to psychiatric medication treatment affects the performance of domains associated with social cognition. These domains include Theory of Mind (TOM) and other neuropsychological functions such as verbal memory and executive functions (Zhang et al, 2016;Caqueo et al, 2017;El-Missiry et al, 2015). This demonstrates the relevance of the topic under the findings provided by previous research, which indicates the scientific importance that neurocognitive processes in schizophrenia and their relationship with medication adherence are acquiring.…”
Section: Issn-l: 2027-1786mentioning
confidence: 56%